NFLUENCE OF TOTAL ASSETS, PROFITABILITY AND LIQUIDITY ON PROFITS - Sa’diyah, Halimatus; Haerudin, Haerudin (Economics and Business International Conference Proceeding, 2024)
This research aims to determine the effect of Total Assets, Profitability and Liquidity on Profits in Pharmaceutical Sector Companies Listed on the Indonesian Stock Exchange for the 2019 - 2022 Period. The analysis technique is carried out using multiple linear regression analysis. The sample selection in this research used the purposive sampling method. The number of companies used as samples based on predetermined criteria was 10 companies. Hypothesis testing uses the t test, F test, and determination test. Apart from that, the normality test, multicollinearity test, autocorrelation test and heteroscedasticity test are also used. The results of this research show that partially Total Assets, Profitability and Liquidity have a significant effect on Profit. Total Assets has a positive and significant effect on Profit. Profitability has a positive and insignificant effect on Profit. Liquidity has a negative and insignificant effect on Profit. The coefficient of determination (R2) is 0.150, which means that the ability of the independent variable to explain variations in related variables is 15%, while the remaining 85% is explained by other independent variables not examined in this research. This research provides useful input and considerations for companies to predict company profits and increase the strength of their assets.